2015
DOI: 10.1088/0964-1726/24/12/125016
|View full text |Cite
|
Sign up to set email alerts
|

Robust design method and thermostatic experiment for multiple piezoelectric vibration absorber system

Abstract: This paper examines the effects of connecting multiplexing shunt circuits composed of inductors and resistors to piezoelectric transducers so as to improve the robustness of a piezoelectric vibration absorber (PVA). PVAs are well known to be effective at suppressing the vibration of an adaptive structure; their weakness is low robustness to changes in the dynamic parameters of the system, including the main structure and the absorber. In the application to space structures, the temperature-dependency of capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…According to the input variation and output requirements, the characteristics of stiffness and damping in the system can be regulated to achieve the expected vibration isolation performance. Semi-active controllers have been widely used to control the oscillations of engineering structures (Zhou et al., 2006; Nambu et al., 2015; Wang et al., 2016, 2017a, 2017b). Prior research has already indicated the potential of the semi-active control technique (Onada et al., 1991; Kermani, 2010; Chu et al., 2015; Hung and Weng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the input variation and output requirements, the characteristics of stiffness and damping in the system can be regulated to achieve the expected vibration isolation performance. Semi-active controllers have been widely used to control the oscillations of engineering structures (Zhou et al., 2006; Nambu et al., 2015; Wang et al., 2016, 2017a, 2017b). Prior research has already indicated the potential of the semi-active control technique (Onada et al., 1991; Kermani, 2010; Chu et al., 2015; Hung and Weng, 2015).…”
Section: Introductionmentioning
confidence: 99%